PENILAIAN HARGA WAJAR SAHAM PT.KIMIA FARMA (PERSERO) Tbk DAN PT. INDOFARMA (PERSERO) Tbk MENJELANG AKUISISI - Lestari Puji Astuti (MIX: JURNAL ILMIAH MANAJEMEN, 2013)
Abstract: Regrouping pharmaceutical companies in Indonesia among PT. Kimia Farma(Persero) Tbk and PT. Indofarma (Persero) Tbk will be carried out by the governmentthrough inbreng scheme. In order to take acquisitions, a fair price must be counted for,so the public interests not be harmed For the fair price ofshares, the calculating areusing three (3) of valuation methods thats are freecash flowto equity, relative valuationmethods and gordon growth models. After doing the calculations with those methods,affair price for the shares of PT. Kimia Farma (Persero) Tbkand PT. Indofarma(Persero) Tbk its obtained. To get affair price to the value of the reference shares,reconciliation should be done. Based onthe results of there conciliation, the fair pricesfor thes hares of PT. Kimia Farma (Persero) Tbk is 693 rupiahs and PT. Indofarma(Persero) Tbk iis 404 rupiahs with avalue range of 7.5 per centofthe fair price.Keywords: Acquisitions, freecash flowto equity, relativevaluation, Gordon growthmodels